Gaya Bahasa Dalam Novel The Lady of The Lake Karya Sir Walter Scott - Abdur Rohman, Mujahidin (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2024)
This research aims to describe and explain the language style or majas in the novel The Lady of the Lake by Sir Walter Scott. The research explains the analysis of language styles and shares the types of majas that will be used in the film. The research method used is qualitative descriptive, using semantic approaches and assistance. Data analysis uses qualitative data techniques. Data Source taken from the Novel by Sir Walter Scott. The results of the study explain that there are several language styles mentioned in the novel, namely metaphor, hyperbole, personification, allegory, and paradox.